Strategic HRM The implications for pharmaceutical R&D - Jones, Oswald (Technovation)
The paper is concerned with the strategic human resource management (HRM) implications of recent pressure for change in the pharmaceutical industry : the mergers and marketing agreements which began in the late 1980s; Government attempts to control NHS spending through the 'Limited List'; and competition from generic drugs. Despite the increasing use of information technology and expert systems, scientific research remains highly labour intensive and very costly. However, the continued success of all the leading pharmaceutical companies is heavily dependent upon the ability of R&D to innovate new drugs.